The Characteristics and Clinical Analysis of Lorenz Plot of Neonatal Atrial Tachycardia - Fei Zheng; Tingting Yu; Xin Wei; Jie Wen; Hualian Li (Annals of Noninvasive Electrocardiology)
ABSTRACT Background Lorenz plot (LP) analysis enhances the accuracy of arrhythmia diagnosis and serves as an attractive diagnostic tool for patients with arrhythmias. We explored the utility of the LP in the classification of various types of neonatal atrial tachycardia and evaluated the treatment effects and prognosis. Methods Ninety‐six newborns with atrial tachycardia had their dynamic electrocardiograms and clinical data collected between January 2018 and June 2023. They were divided into different atrial tachycardia groups based on the morphological characteristics of the LP. The clinical features of the patients in each group were also analyzed. Results Neonates were divided into multifocal (30%, 31.25%), parasystole (19%, 19.79%), and atrial premature beat‐induced atrial tachycardia (47%, 48.96%) groups. It was demonstrated that the prevalence of cardiac structural abnormalities, viral infections, myocardial injury, and heart failure was significantly increased in the multifocal atrial tachycardia group. Conclusions The analysis of distinct LP patterns allowed for the identification and classification of neonatal atrial tachycardia, which could improve the diagnostic efficiency of neonatal atrial tachycardia and assist clinical physicians in making better management strategies based on the type of atrial tachycardia.